“A shared human endeavor”: farmer participation and knowledge co-production in agroecological research - Maughan, Chris; Anderson, Colin Ray (Frontiers in Sustainable Food Systems, 2023)
Farmer participation in the co-production of knowledge has been claimed to have many benefits, including its capacity to address the knowledge intensiveness and ecological specificity that underpins agroecology. The complexity of agroecological knowledge systems have until now presented considerable challenges to researchers looking to develop research practices adaptable to and commensurate with the integrative ambition of agroecology. As with agroecology in general, participation in research cannot be delivered in a one-size-fits-all approach, with each case needing to be designed on the basis of numerous factors, especially including the needs, objectives, and capacities of diverse participants. This article presents a conceptual framework to explore farmer participation in the co-construction of knowledge in agroecology. Through an exploration of three UK-based participatory research projects we develop a framework to better understand the practical challenges and opportunities for deepening the co-construction of knowledge. Using a combination of field notes, interviews, and survey data, the article concludes by offering practical reflections on ways to co-design research based on the type of knowledge(s) produced, the types of participation envisaged, as well as the needs and capacities of the research participants themselves. The framework presented in the article is offered as a tool to guide early stages of research design in order to balance the complex and changing needs of researchers and their collaborators.